Microwave-Assisted Synthesis and Antibacterial–Anticancer Evaluation of Sulfadiazine-Imine Derivatives - Dhamer Ismael Madab; Mohammad M. Al-Tufah; Diaa M. Najim (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study synthesized novel sulfadiazine-imine derivatives (A1 and A2) using a microwave-assisted method by reacting sulfadiazine with orsellinaldehyde and 2-hydroxy-5-methylbenzaldehyde. The synthesis involved the nucleophilic addition of sulfadiazine to the aldehyde groups, forming imine bonds efficiently under microwave irradiation within 15 minutes. The antibacterial efficacy of the synthesized derivatives was tested against Bacillus subtilis, Streptococcus pneumoniae, and Escherichia coli using agar well diffusion methods. The derivatives A1 and A2 exhibited significantly improved antibacterial activities compared to sulfadiazine, with A1 showing the highest efficacy. Specifically, inhibition zones for Bacillus subtilis reached 26 mm (A1 at 100 mg/mL) compared to 20 mm for sulfadiazine, and similar trends were observed against E. coli and S. pneumoniae. Furthermore, the cytotoxic activity against MCF-7 breast cancer cells revealed that both derivatives demonstrated dose-dependent cytotoxicity. For derivative A1, cell viability decreased to 19% at 320 ppm with an estimated IC50 between 40 and 80 ppm. Derivative A2 showed comparable cytotoxic behavior, with cell viability dropping to 12.6% at the highest concentration tested. The enhanced antibacterial and anticancer properties are attributed to increased lipophilicity and improved cellular penetration conferred by the imine functional group. This research highlights the potential of microwave-assisted derivatization of sulfadiazine to produce compounds with promising therapeutic applications.